CHARACTERISTICS, PATTERNS OF PATHOGENS, AND ANTIBIOTICS RESISTANCE OF BACTERIAL MENINGITIS AT RSUP DR. MOHAMMAD HOESIN PALEMBANG - Andika Okparasta; Dewi Susan; Irfannuddin Irfannuddin (JURNAL KEDOKTERAN DAN KESEHATAN, 2020)
Bacterial meningitis is an inflammation of the meninges, especially arachnoid and pia mater, which occurs due to the invasion of bacteria into the subarachnoid space. Bacterial meningitis cases are distributed throughout the world, with an incidence of 2-6 / 100,000 people per year with a peak incidence in infants, adolescents, and the elderly. This study was a retrospective cross-sectional descriptive study to look for sociodemographic characteristics, pathogens and resistance patterns, and clinical outcomes of bacterial meningitis patients at dr. Mohammad Hoesin Palembang. There were 43 cases of bacterial meningitis, and only 13 cases met the inclusion and exclusion criteria. Most cases of bacterial meningitis were in the 30-45 years (30%) and 46-55 years (30%) age groups, with predominantly female patients (69%). The most noted clinical manifestations were fever and neck stiffness (100%).  decreased consciousness (92%), hemiparesis (77%), headache (70%) and seizures (54%). The mortality rate of bacterial meningitis patients reached 53% with a disability rate reaching 39%. Pathogens found based on culture results were Staphylococcus sp. (69%), Acinetobacter baumanii (5.3%), Klebsiella pneumonie (15%), Shigella somnei,  and E. coli (5.3%). Antibiotic resistance to Staphylococcus sp. Was quite high, namely Erythromycin and Oxacillin reaching 77%, Trimethoprim / Sulfamethoxazole 55%, Ciprofloxacin, Clindamycin, levofloxacin reached 33%. Higher mortality was found in patients with drug resistance.